Knowledge of Strategic Plan influences Labor Productivity in a Telecommunications company - Marín A., Carmen D. (2023)
This document aims to determine how knowledge of strategic plan influences labor productivity in order to meet the goals and objectives of the telecommunications company. The population to be used in this research is given by all the collaborators (29 people) of the telecommunications company INCOBECH. Questionnaires were used to measure the variables of this research: knowledge of strategic plan and labor productivity. At the same time, the personnel was evaluated quantitatively through the incidences that the collaborators have had in order to show the level of labor productivity through the indices of effectiveness and efficiency of the collaborator at work. When having the results, the hypothesis test was carried out through the correlation of the variables, resulting in a correlation of 0.762, being a positive and very strong correlation between the knowledge of strategic plan and labor productivity, demonstrating that the company's collaborators INCOBECH, by having a high level of knowledge of strategic plan, improves its effectiveness, efficiency and therefore increases labor productivity.